Rehabilitation Before and After Autologous Haematopoietic Stem Cell Transplantation (AHSCT) for Patients With Multiple Sclerosis (MS): Consensus Guidelines and Recommendations for Best Clinical Practice on Behalf of the Autoimmune Diseases Working Party, Nurses Group, and Patient Advocacy Committee of the European Society for Blood and Marrow Transplantation (EBMT) - Roberts, Fiona; Hobbs, Helen; Jessop, Helen; Bozzolini, Cristina; Burman, Joachim; Greco, Raffaella; Ismail, Azza; Kazmi, Majid; Kirgizov, Kirill; Mancardi, Gianluigi; Mawson, Susan; Muraro, Paolo A.; et al. (Frontiers in Neurology, 2020)
Autologous haematopoietic stem cell transplantation (AHSCT) is increasingly used to treat people with multiple sclerosis (MS). Supported by an evolving evidence base, AHSCT can suppress active inflammation in the central nervous system and induce long-term changes in immune cell populations, thereby stabilising, and, in some cases, reversing disability in carefully selected MS patients. However, AHSCT is an intensive chemotherapy-based procedure associated with intrinsic risks, including profound cytopenia, infection and organ toxicity, accompanied by an on-going degree of immuno-compromise and general deconditioning, which can be associated with a transient increase in functional impairment in the early stages after transplantation. Although international guidelines and recommendations have been published for clinical and technical aspects of AHSCT in MS, there has been no detailed appraisal of the rehabilitation needed following treatment nor any specific guidelines as to how this is best delivered by hospital and community-based therapists and wider multidisciplinary teams in order to maximise functional recovery and quality of life. These expert consensus guidelines aim to address this unmet need by summarising the evidence-base for AHSCT in MS and providing recommendations for current rehabilitation practice along with identifying areas for future research and development.